Identifying erosion risk criteria for coastal city sustainability by using a Hyper-Delphi-hierarchy model: a case study of Kuala Terengganu, Malaysia - Bagheri, Milad; Ibrahim, Zelina Z.; Manaf, Latifah Abd; Wolf, Isabelle D.; Akhir, M.F.; WIAW, Talaat (Springer Science and Business Media B.V., 2024)
Coastal erosion poses a significant threat to the sustainability of urban coastal areas, endangering communities and economies alike. Addressing this complex issue requires innovative strategies that integrate diverse perspectives and robust decision-making frameworks. Traditional methods of assessing coastal erosion risks often lack a robust decision-making framework that can handle the complexity and variability of coastal environmental issues. In this study, we propose an innovative method that combines a Hyper-Delphi Hierarchy (HDH) approach and multi-criteria decision analysis (MCDA) to evaluate erosion risks in coastal cities, as demonstrated in a case study conducted in Kuala Nerus and Kuala Terengganu, Malaysia. We demonstrated high- and low-risk important criteria values and determined the main factors influencing coastal erosion risk by a thorough analysis of objective field data and expert opinions. Notably, the presence of rivers emerges as a significant risk factor, with a score of 0.282, followed closely by changes in the shoreline at 0.275, and floods at 0.251. Surprisingly, the effect of built-up areas appears lower than anticipated, registering a score of 0.073. These scores derived from the HDH model, represent the weighted importance of various risk factors based on expert evaluations and reflect the relative significance of each factor in contributing to coastal erosion risk. This HDH study demonstrated hazard criteria and layer weight and integrated Geographic Information Systems (GIS) spatial data for assessing coastal erosion risk, providing important insights into coastal city sustainability (CCS). Areas like Bukit Besar, Kuala Nerus, and Batu Rakit were identified as having the highest risk, with large areas of extremely hazardous conditions. In contrast, Pengadang Buluh displayed the lowest risk due to effective coastal defense measures. Our research provides a methodological blueprint that helps identify key erosion risk factors to prioritize in mitigation strategies. Future research will benefit from incorporating these findings into vulnerability and hazard mapping studies, for example, by adopting weighting factors for GIS layers, to contribute to erosion mitigation planning in coastal cities.